2001
DOI: 10.1054/bjoc.2001.1843
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the critical DNA lesions produced by antibody-directed enzyme prodrug therapy (ADEPT) in vitro, in vivo and in clinical material

Abstract: Summary An antibody-directed enzyme prodrug therapy (ADEPT) system against CEA-positive tumours is currently in phase I clinical trials. It consists of a prodrug, 4-[N,N-bis(2-iodoethyl) amino] phenoxycarbonyl L-glutamic acid (ZD2767P) and a conjugate of the F(ab') 2 anti-CEA antibody A5B7 and the bacterial enzyme carboxypeptidase G2 (CPG2). ZD2767P is converted by antibody-targeted CPG2 into an active bifunctional alkylating drug (ZD2767) at the tumour site. The IC 50 value of the prodrug against the human co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…Oxaliplatin also forms interstrand crosslinks, which represent 10% of the total number of adducts [53]. The mode of action of many chemotherapeutic drugs of importance in cancer treatment is through production of DNA interstrand crosslinks detectible by the comet assay in cells exposed to the drug [54]. It has recently been demonstrated that oxaliplatin-induced crosslinks were detected by the alkaline Comet assay using a H460 tumour cell line and patients' lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Oxaliplatin also forms interstrand crosslinks, which represent 10% of the total number of adducts [53]. The mode of action of many chemotherapeutic drugs of importance in cancer treatment is through production of DNA interstrand crosslinks detectible by the comet assay in cells exposed to the drug [54]. It has recently been demonstrated that oxaliplatin-induced crosslinks were detected by the alkaline Comet assay using a H460 tumour cell line and patients' lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is now increasingly used to monitor ICL formation and unhooking in clinical samples (30,40) as a pharmacodynamic end point in clinical trials (41,42), and following ex vivo treatment (39,43).…”
Section: Discussionmentioning
confidence: 99%
“…It is also more sensitive than other techniques used to measure ICL such as alkaline elution and allows the formation and repair of ICL to be studied in clinical material at pharmacologically relevant doses. 20 For example, initial ICL formation and repair studies using in vitro cell lines and human tumor xenograft models were extended to tumor biopsies from patients undergoing antibody-directed enzyme prodrug therapy phase 1 clinical trials, 21 and in vivo formation of ICL has also been followed in lymphocytes taken from patients receiving ifosfamide therapy. 20 In the present study we have used the Comet assay to examine formation and repair of melphalan-induced ICL in plasma cells from patients with MM following ex vivo treatment with melphalan.…”
Section: Introductionmentioning
confidence: 99%